Micro CT evaluation of marginal discrepancies of endocrown restored molars with different intrapulpal depths and materials of fabrication. (in-vitro study) - Mohamed Aly Mohamed Badr Elagwany; Amina Mohamed Hamdy; Maged Mohamed Zohdy; Aliaa Mahrous; Ahmed Tawfik; Soha Osama Nabih (BMC Oral Health)
Abstract Objective The purpose of this study was to evaluate the effect of different preparation depths (0, 2 and 4 mm) of different restoration designs (classic endocrown design versus overlay design) on marginal adaptation of restorations fabricated of two different restorative materials (lithium disilicate and PEEK). Materials and methods Sixty mandibular natural molars were collected as abutments for the restorations of this study, and grouped in three main groups of different cavity depths (0, 2 and 4). Each group was divided into two subgroups according to material of fabrication to (L) for lithium disilicate (IPS emax CAD, Ivoclar vivadent, Switzarland) and (P) for PEEK (Bio-hpp, Bredent, Germany). CAD/CAM milling technology was used for fabrication of restorations. After cementation of restorations over abutments, hydrothermal aging was performed, and then marginal adaptation was evaluated via micro CT technology. Results Regarding cavity depths, there was a significant difference between different groups (p < 0.001). The highest value was found in samples with 4 mm extension (84.35 ± 18.16), followed by samples with 2 mm extension (66.52 ± 21.86), while the lowest value was found in samples without pulpal extension (59.41 ± 22.16). Post hoc pairwise comparisons showed samples with 4 mm extension to have a significantly higher value than samples without extension (p < 0.001). Regarding materials of fabrication, PEEK (85.32 ± 12.37) had a significantly higher value than Emax (54.86 ± 20.86) (p < 0.001). Conclusions Increasing intrapulpal cavity depths increases vertical marginal gap of lithium disilicate or PEEK restorations. Endocrowns fabricated of lithium disilicate show less marginal discrepancies than that of endocrowns fabricated of PEEK.